2019
DOI: 10.1186/s12917-019-2149-5
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne pathogens in ticks collected from dogs, Latvia, 2011–2016

Abstract: BackgroundDifferent tick species are able to transmit different pathogens, and tick-borne diseases are of substantial concern worldwide for both humans and animals. Environmental changes and changes in the range of tick species, including Dermacentor reticulatus in Europe, can affect the spread of zoonotic pathogens. The aim of this study was to investigate the prevalence of the tick-borne pathogens in ticks removed from dogs in Latvia, and to explore possible changes between years 2011 and 2016.ResultsIn 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 44 publications
4
21
1
Order By: Relevance
“…The presence of Ba. canis in I. ricinus observed here is in accordance with a study conducted by Cieniuch et al [ 48 ] in Poland, which showed that approximately 1% of field-collected I. ricinus ticks were infected, and also agrees with our recent study on ticks collected from dogs [ 10 ]. Interestingly, in the present study, the prevalence of Ba.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The presence of Ba. canis in I. ricinus observed here is in accordance with a study conducted by Cieniuch et al [ 48 ] in Poland, which showed that approximately 1% of field-collected I. ricinus ticks were infected, and also agrees with our recent study on ticks collected from dogs [ 10 ]. Interestingly, in the present study, the prevalence of Ba.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, D. reticulatus has been detected in geographically separate new localities in the Riga region, indicating the development of new foci outside of the major distribution area. Similar to these findings, we reported in a recent study that from 2011 to 2016, D. reticulatus ticks were removed from dogs in western, southern and central parts of Latvia and the Riga region [ 10 ]. Outside of Latvia, the spread of D. reticulatus during the last decade has been notable in other European countries such as neighboring Lithuania [ 9 , 11 , 19 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our study, only 5 out of 402 (1.2%) engorged I. ricinus females showed the presence of A. phagocytophilum DNA. The prevalence of A. phagocytophilum was 6% in the DNA of adult I. ricinus ticks collected from dogs in Latvia, whereas in I. persulcatus and D. reticulatus, the pathogen was not identified [56]. Even though similar studies are scarce, our data did seem rather low for the country.…”
Section: Discussioncontrasting
confidence: 64%